YBRAY'S WAY - Ramazanova, A.A.; Moldahmetova, Z.K. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
Shown and demonstrated Ibrai's long way in the field of pedagogy. The article tells about the contribution of I. Altynsarin to the Kazakh literature, the spiritual culture of the Kazakh people, as well as the influence on the formation of the literature of the Kazakh people. Particular attention is paid to his teaching activities and his works.
Keywords: literature; school opening; education; enlightenment; Ibrai's stories